Your denominators are 4, 6 and 3. The least common multiple of 4, 6 and 3 is 12, so multiply everything by 12.
12(x-1)/4 - 12(x-2)/6 = 12(2/3)
Simplify
3(x-1) - 2(x-2) = 4(2)
Distribute
3x - 3 - 2x + 4 = 8
Combine like terms
x + 1 = 8
Subtract 1 from each side
x = 7
2006-11-05 15:24:22
·
answer #1
·
answered by MsMath 7
·
3⤊
3⤋
Combine like terms and get a common denominator (try 12):
x - 1/4 - (x - 2/6) =
x - 1/4 - x + 2/6 =
x - x - 1/4 + 2/6 =
1/4 + 2/6 =
1/4 + 1/3 =
3/12 + 4/12 =
7/12
So 2/3 is not the correct answer. (2/3 would be the correct answer if your first term was (x-1/3) instead of (x-1/4).)
2006-11-05 15:22:55
·
answer #2
·
answered by djc 3
·
2⤊
1⤋
I think you might have copied the question wrong:
remove brackets:
x - 1/4 - x + 2/6 = 2/3
cancel "x":
-1/4 + 2/6 = 2/3
common denominators:
-3/12 + 4/12 = 8/12
1/12 = 8/12 <== WRONG!!!
2006-11-05 15:28:28
·
answer #3
·
answered by cliffrosewood 1
·
1⤊
1⤋
Multiply both sides by 12 to get rid of the fractions:
12((x-1/4)-(x-2/6))=12(2/3)
12x-3-(12x-4)=8
12x-3-12x+4=8
0x+1=8
0x=7
No Solution
Check:
(0-1/4)-(0-2/6)=2/3
-1/4+2/6=2/3
-3/12+4/12=2/3
1/12â 2/3
2006-11-05 15:28:34
·
answer #4
·
answered by Anonymous
·
0⤊
1⤋
the way you wrote your problem
means that
x -1/4 -x +2/6 = 2/3
-1/4 + 1/3 = 2/3 which is clearly INCORRECT
MAY be you meant:
(x-1)/4-(x-2)/6=2/3
then take common denominator:
( 3x-3 - 2x+4) /12 = 2/3
then
x+1 = 2 (12) /3
x+1 =8
x =7
s
2006-11-06 05:32:53
·
answer #5
·
answered by locuaz 7
·
0⤊
3⤋
if by this you mean
((x - 1)/4) - ((x - 2)/6) = (2/3)
Multiply everything by 12
3(x - 1) - 2(x - 2) = 4(2)
3x - 3 - 2x + 4 = 8
x + 1 = 8
x = 7
ANS : x = 7
2006-11-05 15:24:54
·
answer #6
·
answered by Sherman81 6
·
1⤊
2⤋